A Meta-Analysis of How Country-Level Factors Affect Web Survey Response Rates. (May 2022) - Daikeler, Jessica; Silber, Henning; Bošnjak, Michael
A major challenge in web-based cross-cultural data collection is varying response rates, which can result in low data quality and non-response bias. Country-specific factors such as the political and demographic, economic, and technological factors as well as the socio-cultural environment may have an effect on the response rates to web surveys. This study evaluates web survey response rates using meta-analytical methods based on 110 experimental studies from seven countries. Three dependent variables, so-called effect sizes, are used: the web response rate, the response rate to the comparison survey mode, and the difference between the two response rates. The meta-analysis indicates that four country-specific factors (political and demographic, economic, technological, and socio-cultural) impact the magnitude of web survey response rates. Specifically, web surveys achieve high response rates in countries with high population growth, high internet coverage, and a high survey participation propensity. On the other hand, web surveys are at a disadvantage in countries with a high population age and high cell phone coverage. This study concludes that web surveys can be a reliable alternative to other survey modes due to their consistent response rates and are expected to be used more frequently in national and international settings.